Characterization of the cork surface by inverse gas chromatography - Cordeiro, Nereida (2021)
Inverse gas chromatography (IGC) at infinite dilution has been used to study the surface properties of cork from Quercus suber. The dispersive component of its surface energy was determined at different temperatures using n -alkanes as probes, and a γDS value of 38 ± 1 mJ · m-2 at 40°C was obtained. The surface acid (A)/base (B) properties were also evaluated by using polar probes and the results indicate that cork has an amphoteric character, with a KA /KB = 1.1. The advantages of IGC, compared with the technique of contact angle measurements in the characterization of the cork surface, are discussed.